2018
DOI: 10.1021/acs.oprd.8b00092
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Synthesis of Kinase Inhibitor AKN028

Abstract: The novel tyrosine kinase inhibitor AKN028 has demonstrated promising results in preclinical trials. An expedient protocol for the synthesis of the compound at kilogram scale is described, including an S N Ar reaction with high regioselectivity and a Suzuki coupling. Furthermore, an efficient method for purification and removal of residual palladium is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…As a test of the ESP/EA model's potential utility in real-world synthetic planning, we sought to validate its predictions against S N Ar reactions used to prepare clinical candidate active pharmaceutical ingredients (APIs). These include recent reports on branebrutinib, 134 an EGFR T790 M inhibitor, 135 a Nav1.7 inhibitor, 136 a tyrosine kinase inhibitor, 137 an SRI/5-HT 2A antagonist, 138 an RoRγ inverse agonist, 139 and merestinib 140 ( Fig. 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a test of the ESP/EA model's potential utility in real-world synthetic planning, we sought to validate its predictions against S N Ar reactions used to prepare clinical candidate active pharmaceutical ingredients (APIs). These include recent reports on branebrutinib, 134 an EGFR T790 M inhibitor, 135 a Nav1.7 inhibitor, 136 a tyrosine kinase inhibitor, 137 an SRI/5-HT 2A antagonist, 138 an RoRγ inverse agonist, 139 and merestinib 140 ( Fig. 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several more case studies of the successful use of functionalized silicas and resins have been reported by pharmaceutical companies, demonstrating their utility and applicability on an industrial scale. An additional benefit exhibited by functionalized silica scavengers is the ease of metal recovery via incineration. This is a favorable property, as metal catalysts typically account for approximately 5–20% of total manufacturing costs; hence, recovery and potential recycling of the metal are highly beneficial in making the process as economical as possible .…”
Section: Adsorptionmentioning
confidence: 99%
“…Eszopiclone Insomnia [24,25] Zopiclone Treatment of sleep disorders [26] Cephalostatin 1 Anticancer [27,28] Favipiravir Antiviral (approved in Japan, influenza; FDA clearance, COVID-19) [29][30][31] (-)-Barrenazine A Anticancer [32] (-)-Barrenazine B Anticancer [32] Alocasin A Anticancer [33] AKN-028 Acute myeloid leukemia [34,35] Acute myeloid leukemia [34,35] Botryllazine Anticancer [36,37] Phenazine-1-carboxylic acid Antibacterial [38] 2-Bromo-1-hydroxy phenazine Antibacterial [39] Griseolutein A Antibacterial [40] HP-14 Biofilm-eradicating agent [41] Iodinin Antibacterial [42] Myxin Antibacterial [43] Quinoxidine Antibacterial [44] Dioxidine Antibacterial [44] Anticancer [36,37] Phenazine-1-carboxylic acid Botryllazine Anticancer [36,37] Phenazine-1-carboxylic acid Antibacterial [38] 2-Bromo-1-hydroxy phenazine Antibacterial [39] Griseolutein A Antibacterial [40] HP-14 Biofilm-eradicating agent [41] Iodinin Antibacterial [42] Myxin Antibacterial [43] Quinoxidine Antibacterial [44] Dioxidine Antibacterial [44] Antibacterial [38] 2-Bromo-1-hydroxy phenazine Botryllazine Anticancer [36,37] Phenazine-1-carboxylic acid Antibacterial…”
Section: Pyrazinamidementioning
confidence: 99%